2006
DOI: 10.2169/internalmedicine.45.1761
|View full text |Cite
|
Sign up to set email alerts
|

Candida albicans Endophthalmitis after Extracorporeal Shock Wave Lithotripsy in a Patient with Liver Cirrhosis

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…There are, of course, several studies that have reported the evaluation of micafungin in human patients. Toshikuni and colleagues reported that co-administration of micafungin with fluconazole eye drops was proved to be more effective in treating C. albicans endophthalmitis than systemic fluconazole treatment in a patient with cirrhosis of the liver [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…There are, of course, several studies that have reported the evaluation of micafungin in human patients. Toshikuni and colleagues reported that co-administration of micafungin with fluconazole eye drops was proved to be more effective in treating C. albicans endophthalmitis than systemic fluconazole treatment in a patient with cirrhosis of the liver [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…Endogenous Candida endophthalmitis is an uncommon, sight-threatening condition with poor visual acuity outcome [13]. Predisposing factors that have been reported for ECE include major gastrointestinal intervention, long-term systemic antibiotic use, recent hospitalization, indwelling catheters, candiduria, hyperalimination, prolonged intravenous line, hemodialysis, chronic liver disease, surgical abortion, neutropenia, immunomodulatory therapy, diabetes mellitus, hematopoietic stem cell and organ transplantation, alcoholism, intravenous drug abuse, and HIV [17].…”
Section: Discussionmentioning
confidence: 99%
“…Toshikuni and associates reported a case of fungal sepsis and C. albicans endophthalmitis after extracorporeal shock wave lithotripsy in a cirrhotic patient [10]. Beck and associates reported two patients with Child-Pugh class B and C liver cirrhosis who had undergone ureteroscopy and holmium laser lithotripsy for obstructing ureteral calculi [11].…”
Section: Discussionmentioning
confidence: 99%
“…Toshikuni and associates suggested that administration of antifungal agents before extracorporeal shock wave lithotripsy might be helpful for preventing fungaemia in patients with funguria [10]. The mechanical trauma to the ureter during extracorporeal shock wave lithotripsy might result in dissemination of C. albicans into the bloodstream from urine, infected stent, or urinary calculi.…”
Section: Discussionmentioning
confidence: 99%